Application Of Modern Methods In Primary Mathematics Lessons (Eurasian Journal of Physics,Chemistry and Mathematics, 2024)
This article provides information about modern methods that are most often used in primary mathematics classes. Methods of application of these methods and their effectiveness are discussed